Mapping the global research landscape on depression for patients with chronic kidney disease: a bibliometric and visualized analysis from 2006 to 2022 - Xu, Wenchao; Chen, Zitong; Zhang, Yurong; Zhao, Jiayu; Huang, Wenyong; Guo, Xiao; Zhang, Jianyu (Frontiers in Pharmacology, 2024)
Background Chronic Kidney Disease (CKD), a complex and multifaceted health issue, significantly contributes to global mortality rates. Accompanying chronic conditions, depression notably exacerbates health outcomes, increasing both mortality risk and the burden on affected individuals. This study employs bibliometric and visual analytics to evaluate the evolution, current trends, and future research directions in the field of CKD and depression. Methods We conducted a thorough investigation using the Web of Science Core Collection, focusing on literature published from 2006 to 2022 that examines the interplay between CKD and depression. The analysis was enriched with bibliometric and visualization tools such as bibliometrix, CiteSpace, and VOSviewer to distill the essence of the research corpus. Results Our analysis incorporated 2,409 CKD-related publications, with significant contributions from the United States, China, and England. BMC Nephrology emerged as the leading publication outlet, while the American Journal of Kidney Diseases featured the most cited articles. Key terms such as “depression,” “quality-of-life,” “mortality,” “prevalence,” and “hemodialysis” dominated the keyword landscape, indicating the research focus areas. Conclusion This bibliometric analysis offers an in-depth view of the research trajectory in CKD and depression. It provides valuable insights for researchers seeking relevant literature, potential collaborators, and an understanding of the field’s current hotspots and emerging frontiers. The findings of this study are instrumental in guiding and enriching future research endeavors in this domain.